Quality, equity and indicators in the Spanish education system - Pascual Barrio, Belén (Pulso. Revista de educación, 2006)
In analyses of education indicators, the question that should Þ rst be raised is what we understand by “quality education”, since the concept that is used as a starting point will determine which indicators are used and how. In educational debate by today’s Information Society, the term “quality” is given pride of place. Although the key challenge that is faced by education systems continues to be making basic education available to all the population and guaranteeing a common compulsory education for all citizens, another challenge that is posed by today’s education systems is how to ensure the quality of teaching. In this paper, we look at the relationship between the concepts “quality” and “equity” and at the education indicators used to analyse them.